Dynamic response of structures to thunderstorm outflows: Response spectrum technique vs time-domain analysis. (1st December 2018) - Solari, Giovanni; De Gaetano, Patrizia
Highlights: Design wind velocity and wind-induced damage are often related to thunderstorms. Research on thunderstorm loading of structures is still fragmentary and uncertain. Calibration and advance are provided of response spectrum technique and time-domain analysis. The response spectrum technique is a suitable tool for engineering calculations. Time-domain analysis is highly efficient with a limited computational burden. Abstract: Thunderstorms are transient events. Design wind velocity and wind-induced damage are often related to them. Despite this, research on thunderstorm loading of structures is still fragmentary and uncertain due to their complexity, short duration and small size. These issues make it difficult to set physically realistic and simple models as well as to gather real data. This favoured the implementation of refined methods based on limited measurements. The European Projects "Wind and Ports" and "Wind, Ports and Sea" realised an extensive monitoring network from which many thunderstorm outflow records were extracted. They were analysed to inspect their characteristics and to formulate methods coherent with measurements. Firstly, the response spectrum technique conceived for earthquakes was extended to thunderstorms. Then, a hybrid simulation strategy was proposed and time-domain integrations of the structural response were applied. This paper provides a joint calibration and advancement of these two methods, leading to results that substantially agree, especially faced with their conceptual and operative diversities. This confirms the potential of the response spectrum technique to become a suitable tool for calculating the thunderstorm loading of structures and the efficiency of hybrid simulations and time-domain analyses to investigate, with a limited computational burden, advanced structural issues.